Analisis Pengaruh Infrastruktur terhadap Perdagangan dan Keberhasilan Integrasi Ekonomi Indonesia Ke ASEAN+3 : Institut Pertanian Bogor - Piety Yusyahbella; Arief Daryanto Arief; Tanti Novianti (JURNAL EKONOMI DAN KEBIJAKAN PEMBANGUNAN, 2019)
Export and import from Indonesia to ASEAN+3 countries reached 52.3% and 62.37% of the total trade of Indonesia to the world. Infrastructure played a vital role in supporting successful trade. During the period 2007-2017, loading and discharging flows of Indonesian goods were dominated by sea transportations modes by 96%. Indonesia's infrastructure is far lower than other ASEAN+3 countries especially marine infrastructure and the internet users. The purpose of this study is to describe Indonesia's trade with ASEAN+3 countries, to the determinant that influence Indonesia’s trade into the ASEAN+3 and to analyze the success ratio of Indonesia to ASEAN+3. This study is using descriptive analysis, gravity model and success ratio method. This study is using descriptive analysis, gravity model and success ratio method. The variables used in this study are the gross domestic product per capita, economic distance, air transport freight, container port traffic, internet user and mobile phone. The results show that Indonesia's highest export - import is with China. ATF has no significant effect on both export and import, while other variables give a significant positive effect except GDP per capita that has a significant negative effect to export. The success of economic integration for Indonesia's exports and imports into the ASEAN+3 region has not been fully achieved.